Low power design of ultra wideband PLL using 90 nm CMOS technology - Fadhilah Binti Noor Al Amin; Nabihah Ahmad; Siti Hawa Ruslan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The rapid growth of the electronic system has become one of the challenges in the high performance of very large scale integration (VLSI) design and has contributed to the evolution of phase locked loop (PLL) system design as one of the inevitable and significant necessities in the modern days. This design focus on the development of PLL system that can operate at a high performance within the ultra-wideband (UWB) frequency but consume low power that may be useful for future device implementation in the communication system. All proposed sub modules of PLL is highly suitable for low power and high speed application as each of them consumes overall power consumption around 2 µW until 1 mW with frequency from 3.1 GHz to 10.6 GHz. All the design architecture, schematic, simulation and analysis are implemented using Synopsys Tool in 90 nm CMOS technology. Through the overall analysis, it can be concluded that this proposed sub modules design of the PLL system has better performance compared to previous work in terms of power consumption and frequency.